Rancang Bangun Aplikasi Pengukuran Efektivitas Mesin Produksi dengan Metode Overall Equipment Effectiveness (OEE) pada PT. E-T-A Indonesia - Suharnoko, Ivan Christiono; Wurijanto, Tutut; Oktaviani, Oktaviani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT. E-T-A Indonesia is a company that working in the area of manufacturing, which manufactures circuit breaker. There was a problem in PT. E-T-A Indonesia about measuring the effectiveness from TMC 1160 machine. The result from this condition is difficult to make the preventive maintenance who are used to achieve zero breakdowns. Another problem for company is in difficulties to early identify the waste / loss in order to achive zero loss which cause delayed on machine repairing. An application is offering to make a system which helping company for measurement the effectiveness by using Overall Equipment Effectiveness (OEE) method for the operation of the machine by periodic. These create informations about effectiveness of engine performance and losses by OEE method.The results showed that application has been made to help company for giving measurement about the effectiveness of performance TMC 1160 machine and losses from TMC 1160 machine.Keywords : manufacturing, measurement of effectiveness, overall equipment effectiveness